A Bibliometric Analysis of Green Marketing on Consumer Behavior Using R Studio - Kurniawan, Iwan; Rahayu, Agus; Hendrayati, Heny (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2025)
The analysis was comprehensively conducted on 326 research articles and reviews published in 149 journals listed in the Scopus database from 1995 to 2024, providing measurable and valuable insights into research trends in green marketing and consumer behavior. The results of this study indicate an increase in the literature on this topic, especially since 2022 to 2024. The average number of publications over the last 10 years is 10.7, and the average number of citations per document is 10.7. Researchers from 59 countries have so far conducted research on consumer behavior and green marketing. India has 124 publications, followed by the USA with 113 publications, and China with 65 publications. According to our analysis, elements such as environmentally-based tourism destinations, creative marketing strategies, sustainable consumer behavior, and the increasing importance of green labeling are highlighted. Additionally, areas requiring future research include environmental awareness, waste management, certification of eco-friendly products, and sustainable consumer behavior across all types of eco-friendly product use. Therefore, collaboration between individuals, groups, and companies, both locally and internationally, should be enhanced, with a specific focus on developing innovative green marketing methods to encourage sustainable consumer behavior with a focus on environmental care.